Negotiation under the curse of knowledge - Thibaud Pierrot (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2019)
An individual is affected by the curse of knowledge when he fails to appreciate the viewpoint of a lesser-informed agent. In contrast to a rational person, the cursed individual behaves as if part of his private information were common knowledge. This systematic cognitive bias alters many predictions derived from game theory which involve an asymmetry of information between the players. We investigate in this article how the curse of knowledge modifies individual behaviours in negotiation situations. We report the results of a laboratory experiment that was designed to isolate the effect of the curse of knowledge by varying the information available to the players ceteris paribus. Our analysis of the expectations and choices of subjects playing the ultimatum game in different information settings indicates that the curse of knowledge can lead to an increase of impasses in the negotiation and partially explains empirically observed phenomenons such as abnormally high rates of bargaining failures. Unlike previous behavioural research, that is mostly based on motivated beliefs and actions, this work provides a purely nonstrategic explanation for negotiation impasses observed in many real life situations.
Keywords: C91; D80; D82; D83; D84; 330; curse of knowledge; hindsight bias; negotiation; experiments